2004
DOI: 10.1002/mrc.1485
|View full text |Cite
|
Sign up to set email alerts
|

51V magic angle spinning NMR in VOPO4 phases

Abstract: 51V magic angle spinning NMR was applied to the alpha(II), beta and gamma phases of VOPO4 at three magnetic field strengths (4.7, 7.1, and 11.7 T). The 51V quadrupole and chemical shift tensors were determined by iterative fitting of the NMR lineshapes at the three magnetic field strengths. The applicability of the method is illustrated by comparison with literature data. Although determined chemical shift tensors are completely axially symmetric and of the same magnitude, all studied phases can clearly be dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Ben Abdelouahab et al 47 Lapina et al 51 Siegel et al 52 Several effects could be responsible for this reduction of the homonuclear M 2 compared with the value calculated from eq. [4]: (i) The dipolar coupling could be reduced by motion, not likely in such a rigid solid; (ii) indirect spin-spin coupling may also reduce M 2 , also not likely for nuclear spins that are separated by four bonds; (iii) most likely is that eq.…”
Section: Parametermentioning
confidence: 96%
See 1 more Smart Citation
“…Ben Abdelouahab et al 47 Lapina et al 51 Siegel et al 52 Several effects could be responsible for this reduction of the homonuclear M 2 compared with the value calculated from eq. [4]: (i) The dipolar coupling could be reduced by motion, not likely in such a rigid solid; (ii) indirect spin-spin coupling may also reduce M 2 , also not likely for nuclear spins that are separated by four bonds; (iii) most likely is that eq.…”
Section: Parametermentioning
confidence: 96%
“…Specifically, the third intensity maximum around 0 ppm in their and our experimental 51 V MAS spectra is clearly missing in their simulation. In 2004, Siegel et al 52 reported the results of a detailed study of 51 V NMR spectra of a II -, b-, and g-VOPO 4 at three different external magnetic field strengths. As Table 5 demonstrates, our parameters obtained at 9.4 T are in close agreement with theirs, except for d iso .…”
Section: Vanadium-51 Nmr Spectroscopymentioning
confidence: 99%
“…Overexpression of myocardin induces ES cells to express multiple SMC genes including α-SMA, SM22α, and SMMHC ( 17 ). In atherosclerotic lesions, excess lipids, homocysteinaemia, hypoxic stress and other inflammatory and toxic signals can stimulate endoplasmic reticulum (ER) stress and activate the unfolded protein response in cells ( 18 20 ), which activate ATF6 ( 21 ). ATF6 is a transmembrane transcription factor that is regulated by ER stress and is involved in adipogenesis and odontoblastic differentiation ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we have considered the signal intensity (obtained in simulation or experimentally) as a reliable reflection of the decoupling efficiency. Figure 2 shows the calculated amplitude of the 1 H NMR signal under 27 Al decoupling, as a function of the decoupling sequence parameters τ p and τ d values, at two different decoupling RF field strengths (2 and 70 kHz for Figs. 2a and 2b, respectively).…”
Section: Resultsmentioning
confidence: 99%